Melatonin Redox Activity. Its Potential Clinical Applications in Neurodegenerative Disorders - Miller, Elzbieta; Morel, Agnieszka; Saso, Luciano; Saluk, Joanna (Current Topics in Medicinal Chemistry, 2015)
Neurodegeneration is the hallmark of many chronic progressive neurogical disorders characterized by specific clinical, morphological and biochemical features. Central nervous system is very sensitive to oxidative stress, which is considered as a key factor of neurodegenerative disorders. Therefore, many therapeutical strategies are focused on molecules with redox activity to re-establish the equilibrium between pro and antioxidants. Due to the fact that melatonin readily crosses the blood- brain-barrier, concomitant with its safety profile at the highest dosages makes this dietary supplement very useful in possible clinical application in neurodegeneration. Melatonin is currently marketed in several countries as a dietary supplement with no prescription. Clinical trials have shown different effectiveness of melatonin supplementation in several disorders, including neurodegenerative disorders. Melatonin has unique biochemical properties such as scavenging of hydroxyl, carbonate, alkoxyl, peroxyl and aryl cation radicals and stimulation of activities main antioxidative enzymes (glutathione peroxidase, superoxide dismutase etc.). Moreover, it can suppress nitric oxide synthase. The present paper highlighted the potential clinical role of melatonin in main neurodegenerative diseases including Alzheimer disease, Parkinson disease, amylotrophic lateral sclerosis and multiple sclerosis. Moreover, in this review the main molecular aspects of melatonin in brain cell protection and survival mechanisms were discussed. Therefore, melatonin is regarded as a potential therapeutical agent in clinical application in neurodegenerative disorders, but this findings needs to be confirmed by the larger, more well-designed clinical trials.
Keywords: Oxidative stress